2006 IEEE Nuclear Science Symposium Conference Record 2006
DOI: 10.1109/nssmic.2006.354273
|View full text |Cite
|
Sign up to set email alerts
|

A Further Study of Timing with LSO on XP20D0 for TOF PET

Abstract: In our previous work, a very good time resolution recorded with a 4x4x20 mm 3 LSO crystal coupled to a Photonis XP20D0 photomultiplier was shown, which suggests that TOF-PET based on the LSO is the realistic proposition. A further improvement of the time resolution, due to the common light readout by the cluster of PMTs in the block detector, proposed by Kuhn et al, triggered our further study of obtainable time resolution with the LSO crystals. In the present work, the optimization of timing using a leading-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The cross-over timing method uses zero crossing of signal for time measurements, which compensates for errors arising from amplitude walk but requires bipolar signals [102]. In ToF-PET, however, leading edge triggering at very low photon counts has been reported to provide excellent timing performance in numerous studies [111,112]. A comparator circuit triggered on the rising edge is often used for this purpose.…”
Section: Signal Readout Of Tof-pet Detectorsmentioning
confidence: 99%
“…The cross-over timing method uses zero crossing of signal for time measurements, which compensates for errors arising from amplitude walk but requires bipolar signals [102]. In ToF-PET, however, leading edge triggering at very low photon counts has been reported to provide excellent timing performance in numerous studies [111,112]. A comparator circuit triggered on the rising edge is often used for this purpose.…”
Section: Signal Readout Of Tof-pet Detectorsmentioning
confidence: 99%
“…As the highest timing accuracy is obtained with high bandwidth signals, a ~200 MHz bandwidth version of the amplified signal is sent to a timing circuit. We have selected a leading edge discriminator, as several groups have recently reported that a leading edge discriminator has equivalent or better performance than a constant fraction discriminator (although sometimes requiring amplitude correction for time walk) [9][10][11][12][13]. The ADC values and the timing signal are sent to the detector FPGA.…”
Section: Board Descriptions a Detector Boardmentioning
confidence: 99%